Analiza przyczyn niepowodzeń leczenia fazy aktywnej retinopatii wcześniaków laserem diodowym - Gotz-Więckowska, Anna; Rydlewska-Fojut, Małgorzata; Siennicka, Agnieszka; Burchardt-Kroll, Ewa; Gadzinowski, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: The aim of this study was to analyze risk factors influencing diode laser treatment of active phase of retinopathy of prematurity. Materials and methods: 106 premature infants were treated with the use of diode laser at Department of Neonatology since 1.01.2003-30.11.2004. The mean gestational age was 27.3, mean birth weight 1022 g. The earliest age of laser therapy was 37-th day of life and the latest one 104-th day (mean 64.3 days). 18 neonates were excluded from the study because they were from other departments, and 2 because they died. The results of treatment of the rest 86 children were evaluated. The occurence of retinal detachment or macular ectopy was classified as unfavorable outcome. Results: The complete remission was obtained in 143 eyes (83.2%),the macular ectopy was diagnosed in 10 eyes ( 5.8%), the retinal detachment in 19 eyes (11%). Children with unfavorable outcomes were divided in two groups. The first one included 6 extremely immature infants, born between 24 to 25-th week of gestation. The ROP in this group was diagnosed in I zone with plus disease. The second group included children with gestation age from 28 to 32 Hbd. 9 of them had severe infection (sepsis, congenital pneumonia, urinary tract infection), 1 serious maternal history ( R type of diabetes) . The procedure of laser therapy was performed on average at 72-th day of life at the first group, and at 50-th day at the second one. Conclusions: 1. Important risk factors of treatment failure of active phase of retinopathy of prematurity, is low gestational age and infections which take place in perinatal period. 2. In the second group of infants (gestational age from 28-32 Hbd), with treatment failure the retinopathy of prematurity occured much more earlier then in the group with successful treatment. 3. When making decision of the patient treatment besides estimation of the eye fundus and the progress of changes, we should also consider risk factors which have influence on retinopathy of prematurity, after treatment.